The carnivore remains from the Sima de los Huesos Middle Pleistocene site(Sierra de Atapuerca, Spain) - Torres Pérez-Hidalgo, Trinidad José (E.T.S.I. Minas (UPM), 1997)
Remains of carnivores from the Sima de los Huesos site representing at least 158 adult individuals of a primitive (i.e., not very speleoid) form of Ursus deningeri Von Reichenau 1906, have been recovered through the 1995 field season. These new finds extend our knowledge of this group in the Sierra de Atapuerca Middle Pleistocene. Material previously classified as Cuoninae indet. is now assigned to Canis lupus and a third metatarsal assigned in 1987 to Panthera cf. gombaszoegensis, is in our opinion only attributable to Panthera sp. The family Mustelidae is added to the faunal list and includes Maites sp. and a smaller species. The presence of Panthera leo cf. fossilis, Lynxpardina spelaea and Fells silvestris, is confirmed. The presence of a not very speloid Ursus deningeri, together with the rest of the carnivore assemblage, points to a not very late Middle Pleistocene age, i.e., oxygen isotope stage 7 or older. Relative frequencies of skeletal elements for the bear and fox samples are without major biases. The age structure of the bear sample, based on dental wear stages, does not follow the typical hibernation mortality profile and resembles a catastrophic profile. The site was not a natal or refuge den. The hypothesis that the site was a natural trap is the most plausible. If the Sima de los Huesos functioned as a natural trap (without an egress out), the human accumulation cannot be attributed to carnivore activities and must be explained differently.